Neutral PEGylated liposomal formulation for efficient folate-mediated delivery of MCL1 siRNA to activated macrophages - Nogueira, E. (2017)
Cationic liposomes are efficient vectors for systemic delivery of therapeutic small interfering RNA (siRNA), taking advantage of RNA interference (RNAi), a naturally occurring gene-silencing mechanism in mammalian cells. However, toxicity at high concentrations, short circulating half-lives and lack of specificity restrict their successful application in a wider scale. The purpose of this study was to evaluate the efficiency of neutral liposomes containing polyethylene glycol (PEG) to encapsulate siRNA in their aqueous core. This formulation will reduce drastically the toxicity associated to cationic liposomes by bringing surface charge to almost zero, increasing stealth degree and therefore circulation time. In this study, we evaluate the efficiency of folate-targeted liposomes for specific delivery of siRNA to activated macrophages, key effector cells in rheumatoid arthritis (RA) pathology which specifically express folate receptor (FR). Myeloid cell leukaemia-1 (Mcl-1) is a protein essential for synovial macrophage survival, since Mcl-1 suppression results in the induction of apoptosis. The effect of MCL1 siRNA incorporated in liposomal formulation was assessed in primary human macrophages and successful inhibition of Mcl-1 expression was achieved. Here we show that the neutral liposomal derived from DOPE (1,2-dioleoyl-sn-glycero-3-phosphoethanolamine) formulation developed is efficient to encapsulate MCL1 siRNA and silencing gene expression in activated human macrophages.